Acculturative stress, telomere length, and postpartum depression in Latinx mothers. (March 2022) - Incollingo Rodriguez, Angela C.; Polcari, Justin J.; Nephew, Benjamin C.; Harris, Rebeca; Zhang, Chongben; Murgatroyd, Chris; Santos, Hudson P.
Abstract: Latinx mothers in the United States are highly vulnerable to psychosocial stressors, including discrimination and acculturative stress, which increase maternal health risks. Previous work in Latinx mothers indicates that prenatal discrimination influences epigenetic immune markers that may increase risk for postpartum depression. Discrimination and acculturative stress have also been linked to cellular aging, including telomere degradation, in Hispanic populations broadly, but not in this particularly vulnerable population. The present work addressed this gap in a sample of 150 Latinx mothers living in the United States (mean age 27.6 years). Psychosocial measures (including discrimination, stress, and mental health) and blood were collected at 24–32 weeks gestation. Psychosocial measures were re-evaluated at 4–6 weeks postpartum. First, we examined the relationship between maternal prenatal cultural stress (i.e., discrimination and acculturative stress) and telomere length (TL). Second, we tested whether TL predicted postpartum depression. Acculturative stress – but not discrimination – predicted shorter TL, especially among participants with high methylation of the FOXP3 promoter region. Further, shorter telomere measures during pregnancy predicted greater postpartum depression symptom severity. TL was not related to any sociodemographic characteristics such as age, income, country of origin, or years in the United States. These results highlight the uniquely impactful role of acculturative stress on Latinx maternal health and the potential interactive role of telomere length and epigenetic immune alterations in risk for maternal mental health concerns. Highlights: Psychosocial stress, telomeres, and depression were assessed in Latinx mothers. Acculturative predicted shorter telomere length – moderated by FOXP3 methylation. Shorter telomere length predicted greater postpartum depression symptoms.